Aluminum anode material for alkaline aluminum-air battery and preparation method of aluminum anode material

By adding Mg and Sr elements to the aluminum anode of the aluminum air battery and performing recrystallization annealing, the problem of self-corrosion and hydrogen evolution in the alkaline electrolyte is solved, and the discharge performance and stability of the battery are significantly improved.

CN120048923APending Publication Date: 2025-05-27ZHENGZHOU FOGUANG ELECTRIC POWER EQUIPMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510325698.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-05-27

AI Technical Summary

Technical Problem

The aluminum anode in existing aluminum air batteries shows high self-corrosion rates and hydrogen evolution rates in alkaline electrolytes, resulting in reduced battery voltage and unstable performance.

Method used

By compositely adding Mg and Sr elements to the pure aluminum anode material and performing recrystallization annealing treatment, an aluminum alloy anode with high discharge performance is formed.

Benefits of technology

The discharge voltage, utilization rate and energy density of the aluminum alloy anode are significantly improved, the self-corrosion and hydrogen evolution rate are reduced, and the overall performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to an aluminum anode material for an alkaline aluminum air battery, which takes pure aluminum as a raw material, elements Mg and Sr are added, and the weight percentage of the added elements is as follows: 0.15%-0.85% of Mg and 0.02%-0.35% of Sr. The purity of the pure aluminum is greater than or equal to 99.99%. The invention provides a novel aluminum anode formula. The aluminum anode is activated by compositely adding Mg and Sr elements, and recrystallization annealing is assisted, so that the discharge performance, including discharge voltage, utilization rate, energy density and the like, of the aluminum alloy anode can be obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of aluminum - air batteries, and particularly relates to an aluminum anode material for an alkaline aluminum - air battery and a preparation method thereof. Background Art

[0002] In view of problems such as the gradual reduction of fossil energy, a large amount of carbon dioxide emissions, and the continuous growth of the global demand for new energy, the top priority is to develop new energy sources and promote the transformation of a fossil - fuel - based economy to a clean - energy - based economy. A battery system is an energy - storage device that converts chemical energy into electrical energy. Metal - air batteries have attracted increasing attention due to their outstanding battery performance and good application prospects. Metal - air batteries have advantages such as high specific capacity, wide operating temperature range, stable voltage, and low cost. Among them, aluminum - air batteries have a relatively high specific capacity, the reaction products are green and environmentally friendly, the raw material aluminum has rich reserves, simple assembly, and safe operation. As a special fuel cell, it has applications in military, civilian, and marine underwater power sources, etc., and has great commercial value. This has led to the extensive development of aluminum - air batteries as efficient and environmentally friendly new energy sources.

[0003] The aluminum anode in an aluminum - air battery plays a crucial role in the performance of the battery. An ideal aluminum anode material should effectively inhibit the hydrogen evolution and self - corrosion reactions while maintaining high activity. However, pure aluminum still shows a high self - corrosion rate in an alkaline electrolyte without adding additives. The passivation of the aluminum anode surface leads to a high over - potential, the accumulation of surface discharge products, and an increase in polarization resistance, resulting in a decrease in battery voltage.

[0004] Therefore, in order to balance the activity and corrosion resistance of the aluminum anode to improve its discharge performance, alloying elements are generally added to pure aluminum materials to increase the output voltage and utilization rate of the air battery, and reduce the self - corrosion rate and hydrogen evolution rate. Based on this, the present application is developed. Summary of the Invention

[0005] The purpose of the present invention is to overcome the defects of the prior art and provide an aluminum anode material for an alkaline aluminum - air battery. This aluminum anode material activates the aluminum anode by compounding and adding elements Mg and Sr, and is supplemented by recrystallization annealing, which can significantly improve the discharge performance of the aluminum alloy anode, including discharge voltage, utilization rate, and energy density, etc.

[0006] The present invention also provides a preparation method of the above - mentioned aluminum anode material for an alkaline aluminum - air battery.

[0007] To achieve the above - mentioned purpose, the present invention adopts the following technical solutions: An aluminum anode material for an alkaline aluminum - air battery uses pure aluminum as the raw material and adds elements Mg and Sr. The weight percentages of the added elements are: Mg: 0.15% - 0.85%, Sr: 0.02% - 0.35%.

[0008] Specifically, the pure aluminum can be aluminum with a purity ≥ 99.99%.

[0009] The present invention provides a method for preparing the aluminum anode material for the above-mentioned alkaline aluminum-air battery, which comprises compounding and adding Mg and Sr elements to pure aluminum and casting an aluminum alloy ingot, and performing recrystallization annealing after rolling the aluminum alloy ingot; specifically, the method comprises the following steps: 1) Weigh pure aluminum, Al-Sr master alloy and metallic magnesium according to weight percentages. 2) Melt the pure aluminum and the Al-Sr master alloy to obtain a mixed melt 1. 3) Add the metallic magnesium wrapped with aluminum foil to the mixed melt 1 to obtain a mixed melt 2, and keep it warm for 5 - 20 min. 4) Use argon to perform hydrogen removal treatment on the mixed melt 2 for 3 - 5 min. 5) Cast the mixed melt 2 after hydrogen removal in step 4) into a billet. 6) Remove the oxide scale on the surface of the billet, and cold roll the billet into an aluminum anode plate. 7) Perform recrystallization annealing treatment on the cold-rolled aluminum anode plate (to obtain a recrystallized structure with uniform element distribution and fine grains), thus obtaining the product.

[0010] Specifically, in step 1), the mass fraction of Sr in the Al-Sr master alloy can be 3% - 10%, and the purity of the metallic magnesium can be ≥ 99.99%.

[0011] Specifically, in step 2), the pure aluminum and the Al-Sr master alloy are melted at 700 - 800 °C.

[0012] Specifically, in step 5), the thickness of the billet can be 25 - 35 mm.

[0013] Specifically, in step 6), the deformation amount during cold rolling can be 85% - 90%.

[0014] Specifically, in step 7), the recrystallization annealing temperature can be 250 °C - 400 °C, and the holding time can be 1.5 - 3.5 h.

[0015] The present invention provides the application of the above-mentioned aluminum anode material in the preparation of an alkaline aluminum-air battery.

[0016] The present invention also provides an alkaline aluminum-air battery, which comprises the above-mentioned aluminum anode material.

[0017] The strontium element selected in the present invention is located in Group II of the fifth period in the periodic table, belonging to the alkaline earth metal elements. It is a relatively active metal element, not easy to preserve and prone to oxidation. When added to the alloy as pure strontium, it is prone to oxidation and burning loss, and the operation is inconvenient. Therefore, when preparing the anode plate, it is added in the form of aluminum-strontium master alloy. The introduction of strontium element can be used as a modifier for the alloy, playing a role in refining the alloy grains and improving the comprehensive properties of the alloy. The principle of grain refinement may be that strontium forms an adsorption film at the growth interface, reducing the growth rate of the grains, providing sufficient time for the formation of crystal nuclei in the aluminum melt, so as to achieve the purpose of grain refinement. Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: 1) The present invention provides a new type of aluminum anode formula; by compounding and adding Mg and Sr elements to activate the aluminum anode and supplemented by recrystallization annealing, the discharge performance of the aluminum alloy anode can be significantly improved, including discharge voltage, utilization rate and energy density.

[0018] 2) In the present invention, the Mg element is a commonly used aluminum anode activation element, which can form a segregation phase with the Al matrix; as an alkaline earth metal in the same group as the Mg element, the Sr element can form various segregation phases with the Mg element in addition to forming segregation phases such as Al 4 Sr. The two alloying elements activate the aluminum anode by forming various segregation phases and preferentially dissolving the second phase.

[0019] 3) In the present invention, the recrystallization annealing treatment can quickly achieve the homogenization of the composition and structure of the aluminum anode, and can also release the energy accumulated in the internal defects of the crystal such as dislocations and vacancies during the cold rolling process, transform the fibrous structure into fine equiaxed crystals to refine the grains, reduce the self-corrosion and hydrogen evolution rates, and improve the discharge performance. Description of the Drawings

[0020] Figure 1 It is the stepped discharge curve graph of Example 1 and Comparative Example 1; Figure 2 It is the constant current discharge (50 mA / cm 2 ) graph of Example 3 and Comparative Example 2; Figure 3 It is the constant current discharge (100 mA / cm 2 ) graph of Example 3 and Comparative Example 2; Figure 4 It is the equiaxed grain structure of Example 2. Detailed Embodiments

[0021] The technical solutions of the present invention will be further introduced in detail below in conjunction with the embodiments, but the protection scope of the present invention is not limited thereto.

[0022] In the following embodiments, the raw materials used are all ordinary commercially available products that can be directly purchased. For example, the pure aluminum used is 4N pure aluminum with a purity of ≥99.99%, and the purity of metallic magnesium is ≥99.99%. The mass fraction of Sr in the Al-Sr master alloy is 10%, that is, the Al-10%Sr master alloy is selected.

[0023] Example 1 The aluminum anode material for the alkaline aluminum-air battery in this example is composed of the following components by weight percentage: Mg: 0.2%, Sr: 0.03%, and the balance is Al.

[0024] The preparation method of the above-mentioned aluminum anode material for the alkaline aluminum-air battery is as follows: Step 1: Prepare 4N pure aluminum, Al-10%Sr master alloy, and metallic magnesium according to the weight percentages of the components. Step 2: Melt 4N pure aluminum and Al-10%Sr master alloy at 750 °C to obtain a mixed melt 1. Step 3: Add metallic magnesium wrapped in aluminum foil to the mixed melt 1 to obtain a mixed melt 2, and keep it warm for 10 min. Step 4: Use high-purity argon to carry out hydrogen removal treatment on the mixed melt 2 for 3 min. Step 5: Cast the hydrogen-removed mixed melt 2 in step 4 into a billet in a graphite mold, and the thickness of the billet is 30 mm. Step 6: Use sandpaper to polish and remove the oxide scale on the surface of the billet (the same below), and cold-roll the billet into an aluminum plate with a thickness of 3 mm and a deformation amount of 90%. Step 7: Carry out recrystallization annealing treatment on the cold-rolled aluminum plate. The recrystallization annealing regime is: rise from room temperature to 300 °C in 20 min, keep it warm at 300 °C for 3 h, and then take it out and air-cool, thus obtaining.

[0025] Example 2 The aluminum anode material for the alkaline aluminum-air battery in this example is composed of the following components by weight percentage: Mg: 0.3%, Sr: 0.1%, and the balance is Al.

[0026] The preparation method of the above-mentioned aluminum anode material for the alkaline aluminum-air battery is as follows: Step 1: Prepare 4N pure aluminum, Al-10%Sr master alloy, and metallic magnesium according to the weight percentages of the components. Step 2: Melt 4N pure aluminum and Al-10%Sr master alloy at 750 °C to obtain a mixed melt 1. Step 3: Add metallic magnesium wrapped in aluminum foil to the mixed melt 1 to obtain a mixed melt 2, and keep it warm for 10 min. Step 4: Use high-purity argon to carry out hydrogen removal treatment on the mixed melt 2 for 4 min. Step 5: Cast the hydrogen-removed mixed melt 2 in step 4 into a billet in a graphite mold, with the billet thickness being 30 mm; Step 6: Remove the oxide scale on the surface of the billet, and cold-roll the billet into an aluminum plate with a thickness of 3 mm, with a deformation amount of 90%; Step 7: Perform recrystallization annealing on the cold-rolled aluminum plate. The recrystallization annealing regime is as follows: Heat from room temperature to 400 °C in 20 min, hold at 400 °C for 2 h, then take it out and air-cool, thus obtaining.

[0027] Example 3 The aluminum anode material for the alkaline aluminum-air battery in this example is composed of the following components by weight percentage: Mg: 0.5%, Sr: 0.2%, and the balance is Al.

[0028] The preparation method of the above-mentioned aluminum anode material for the alkaline aluminum-air battery is as follows: Step 1: Prepare 4N pure aluminum, Al-10% Sr master alloy, and metallic magnesium according to the component weight percentages. Step 2: Melt 4N pure aluminum and Al-10% Sr master alloy at 750 °C to obtain mixed melt 1. Step 3: Add metallic magnesium wrapped with aluminum foil to mixed melt 1 to obtain mixed melt 2, and hold for 10 min. Step 4: Use high-purity argon to perform hydrogen removal treatment on mixed melt 2 for 3 min. Step 5: Cast the hydrogen-removed mixed melt 2 in step 4 into a billet in a graphite mold, with the billet thickness being 30 mm; Step 6: Remove the oxide scale on the surface of the billet, and cold-roll the billet into an aluminum plate with a thickness of 3 mm, with a deformation amount of 90%; Step 7: Perform recrystallization annealing on the cold-rolled aluminum plate. The recrystallization annealing regime is as follows: Heat from room temperature to 400 °C in 20 min, hold at 400 °C for 2 h, then take it out and air-cool, thus obtaining.

[0029] Example 4 The aluminum anode material for the alkaline aluminum-air battery in this example is composed of the following components by weight percentage: Mg: 0.8%, Sr: 0.3%, and the balance is Al.

[0030] The preparation method of the above-mentioned aluminum anode material for the alkaline aluminum-air battery is as follows: Step 1: Prepare 4N pure aluminum, Al-10% Sr master alloy, and metallic magnesium according to the component weight percentages. Step 2: Melt 4N pure aluminum and Al-10% Sr master alloy at 750 °C to obtain mixed melt 1. Step 3: Add metallic magnesium wrapped with aluminum foil to mixed melt 1 to obtain mixed melt 2, and hold for 10 min. Step 4: Use high-purity argon to perform a hydrogen removal treatment on the mixed melt 2 for 3 min; Step 5: Cast the mixed melt 2 after hydrogen removal in step 4 into a billet in a graphite mold, and the thickness of the billet is 30 mm; Step 6: Remove the oxide scale on the surface of the billet, cold-roll the billet into an aluminum plate with a thickness of 3 mm, and the deformation amount is 90%; Step 7: Perform a recrystallization annealing treatment on the cold-rolled aluminum plate. The recrystallization annealing regime is as follows: heat up from room temperature to 300 °C in 20 min, hold at 300 °C for 2 h, then take it out and air-cool, thus obtaining.

[0031] Comparative Example 1 The aluminum anode material for an alkaline aluminum-air battery in Comparative Example 1 is composed of the following components by weight percentage: Mg: 0.2%, and the balance is Al.

[0032] The preparation method of the above-mentioned aluminum anode material for an alkaline aluminum-air battery is as follows: Step 1: Prepare 4N pure aluminum and metallic magnesium according to the component weight percentages; Step 2: Melt 4N pure aluminum at 750 °C to obtain melt 1; Step 3: Add metallic magnesium wrapped with aluminum foil to melt 1 to obtain melt 2, and hold for 10 min; Step 4: Use high-purity argon to perform a hydrogen removal treatment on melt 2 for 3 min; Step 5: Cast the mixed melt 2 after hydrogen removal in step 4 into a billet in a graphite mold, and the thickness of the billet is 30 mm; Step 6: Remove the oxide scale on the surface of the billet, cold-roll the billet into an aluminum plate with a thickness of 3 mm, and the deformation amount is 90%; Step 7: Perform a recrystallization annealing treatment on the cold-rolled aluminum plate. The recrystallization annealing regime is as follows: heat up from room temperature to 300 °C in 20 min, hold at 300 °C for 3 h, then take it out and air-cool.

[0033] The difference between this comparative example and Example 1 is that element Sr is not added to the aluminum anode material.

[0034] Comparative Example 2 The aluminum anode material for an alkaline aluminum-air battery in Comparative Example 2 is composed of the following components by weight percentage: Mg: 0.5%, Sr: 0.2%, and the balance is Al.

[0035] The preparation method of the above-mentioned aluminum anode material for an alkaline aluminum-air battery is as follows: Step 1: Prepare 4N pure aluminum, Al-10%Sr master alloy, and metallic magnesium according to the component weight percentages; Step 2: Melt 4N pure aluminum and Al-10%Sr master alloy at 750 °C to obtain mixed melt 1; Step 3: Add magnesium metal wrapped with aluminum foil into the mixed melt 1 to obtain mixed melt 2, and keep it warm for 10 min; Step 4: Use high-purity argon to carry out dehydrogenation treatment on the mixed melt 2 for 3 min; Step 5: Cast the dehydrogenated mixed melt 2 in step 4 into a billet in a graphite mold, and the thickness of the billet is 30 mm; Step 6: Remove the oxide scale on the surface of the billet, and cold-roll the billet into an aluminum plate with a thickness of 3 mm, with a deformation amount of 90%.

[0036] The difference between this comparative example and Example 3 is that: during the preparation process, the aluminum plate was not subjected to recrystallization annealing treatment.

[0037] Performance test Use 6 mol / L KOH + 30 mmol / L Na 2 SnO 3 + 30 mmol / L C 6 H 12 O 6 The electrolyte is used for self-corrosion test, and the hydrogen evolution rate of each aluminum anode material is calculated from the amount of hydrogen gas evolved. The hydrogen evolution rate results of Comparative Examples 1-2 and Examples 1-4 are shown in Table 1.

[0038] Table 1 Hydrogen evolution rate of aluminum anode materials in different examples It can be seen from Table 1 that the hydrogen evolution rates of the aluminum anode materials in Examples 1-4 of the present invention are between 0.0373 and 0.425 mL / cm 2 / min. In contrast, the hydrogen evolution rate of the aluminum anode material in Comparative Example 1 is 0.0596 mL / cm 2 / min, which is greater than 0.0373 mL / cm 2 / min of Example 1, indicating that the addition of Sr element can significantly improve the corrosion resistance of the aluminum anode and reduce the hydrogen evolution rate; the hydrogen evolution rate of the aluminum anode material in Comparative Example 2 is 0.0644 mL / cm 2 / min, which is greater than 0.0403 mL / cm 2 / min of Example 3, proving that the recrystallization annealing treatment can significantly improve the corrosion resistance of the aluminum anode and reduce the hydrogen evolution rate.

[0039] Use 6 mol / L KOH + 30 mmol / L Na 2 SnO 3 + 30 mmol / L C 6 H 12 O 6 electrolyte, commercial MnO 2The air electrode was subjected to stepped discharge tests at different current densities, and a discharge voltage / power density graph was plotted using voltage and current density data (see Figure 1 ); then a constant current discharge test was carried out with a reaction area of 3 cm × 3 cm. The average discharge voltage, discharge energy, the mass of the aluminum anode before and after the reaction were recorded, and the utilization rate and energy density of the aluminum anode were calculated. The discharge performances of Comparative Example 1 to Comparative Example 2 and Examples 1 to 4 are shown in Table 2. Figures 2 to 3 Figure Figure 4 is a comparison graph of the discharge voltages of Example 3 and Comparative Example 2 during constant current discharge. Figure 4 Figure is the metallographic structure diagram of Example 2.

[0040] From Figure 1 it can be seen that the open circuit voltage of Example 1 is higher than that of Comparative Example 1, and during constant current discharge at different current densities, the discharge voltage of Example 1 is also higher than that of Comparative Example 1. The discharge voltages of Example 1 and Comparative Example 1 at 200 mA / cm 2 are 1.022 V and 0.895 V respectively, and the power density corresponding to this current density reaches the maximum, which are 204.4 mW / cm 2 and 179.1 mW / cm 2 respectively.

[0041] Table 2 Constant current discharge performances of aluminum anode materials in different examples From Table 2 and Figures 2 to 3 it can be seen that the average discharge voltages, utilization rates, and energy densities of Examples 1 to 4 during constant current discharge at 50 mA / cm 2 are 1.336 - 1.365 V, 87.78% - 90.16%, and 3.499 - 3.666 kWh / kg respectively. In contrast, the discharge performance of Comparative Example 1 is worse than that of Example 1, which are 1.308 V, 83.92%, and 3.270 kWh / kg respectively, indicating that the addition of Sr element can promote the activation of the aluminum anode and improve the discharge performance; the discharge performance of Comparative Example 2 is worse than that of Example 3, which are 1.333 V, 85.47%, and 3.389 kWh / kg respectively, indicating that recrystallization annealing treatment can also improve the discharge performance of the aluminum anode.

[0042] Examples 1 to 4 at 100 mA / cm 2The average discharge voltage, utilization rate, and energy density of constant-current discharge are 1.179 - 1.206 V, 89.68% - 91.07%, and 3.148 - 3.239 kWh / kg, respectively. In contrast, the discharge performance of Comparative Example 1 is poorer than that of Example 1, being 1.116 V, 85.08%, and 2.830 kWh / kg, respectively, indicating that the addition of Sr element can promote the activation of aluminum anodes and improve the discharge performance; the discharge performance of Comparative Example 2 is poorer than that of Example 3, being 1.154 V, 88.09%, and 3.027 kWh / kg, respectively, indicating that recrystallization annealing can also improve the discharge performance of aluminum anodes.

[0043] Figure 4 The metallographic structure of the aluminum anode material prepared in Example 2 is given. From Figure 4 it can be seen that: the original fibrous structure has been transformed into an equiaxed grain structure.

[0044] In summary, by compounding the addition of Mg and Sr elements to activate aluminum anodes and supplemented by recrystallization annealing, the discharge performance of aluminum alloy anodes, including discharge voltage, utilization rate, and energy density, can be significantly improved.

Claims

1. An aluminum anode material for an alkaline aluminum-air battery, characterized in that: Pure aluminum is used as raw material, and elements Mg and Sr are added, and the weight percentages of the added elements are: Mg: 0.15%~0.85%, Sr: 0.02%~0.35%.

2. The aluminum anode material for alkaline aluminum-air battery according to claim 1, characterized in that: The pure aluminum is aluminum with a purity of ≥99.99%.

3. The method for preparing the aluminum anode material for alkaline aluminum-air battery according to claim 1 or 2, characterized in that: The steps include: 1) Weigh pure aluminum, Al-Sr master alloy and magnesium metal according to weight percentage; 2) Melting pure aluminum and Al-Sr master alloy to obtain a mixed melt 1; 3) Adding metallic magnesium wrapped in aluminum foil to the mixed melt 1 to obtain a mixed melt 2, and keeping the mixture warm for 5-20 minutes; 4) Use argon gas to dehydrogenate the mixed melt 2 for 3 to 5 minutes; 5) casting the mixed melt 2 after dehydrogenation in step 4) into a casting billet; 6) Remove the oxide scale on the surface of the ingot and cold-roll the ingot into an aluminum anode plate; 7) The cold-rolled aluminum anode plate is subjected to recrystallization annealing treatment to obtain the product.

4. The method for preparing an aluminum anode material for an alkaline aluminum-air battery according to claim 3, characterized in that: In step 1), the mass fraction of Sr in the Al-Sr master alloy is 3% to 10%, and the purity of the metal magnesium is ≥99.99%.

5. The method for preparing an aluminum anode material for an alkaline aluminum-air battery according to claim 3, characterized in that: In step 2), pure aluminum and Al-Sr master alloy are melted at 700-800°C.

6. The method for preparing an aluminum anode material for an alkaline aluminum-air battery according to claim 3, characterized in that: In step 5), the thickness of the ingot is 25-35 mm.

7. The method for preparing an aluminum anode material for an alkaline aluminum-air battery according to claim 3, characterized in that: In step 6), the deformation during cold rolling is 85-90%.

8. The method for preparing an aluminum anode material for an alkaline aluminum-air battery according to claim 3, characterized in that: In step 7), the recrystallization annealing temperature is 250°C to 400°C, and the holding time is 1.5 to 3.5 hours.

9. Use of the aluminum anode material according to claim 1 or 2 in the preparation of alkaline aluminum-air batteries.

10. An alkaline aluminum-air battery, characterized in that: Contains the aluminum anode material according to claim 1 or 2.